All‐Polymer Solar Cells Based on Absorption‐Complementary Polymer Donor and Acceptor with High Power Conversion Efficiency of 8.27%. Issue 9 (21st December 2015) - Gao, Liang; Zhang, Zhi‐Guo; Xue, Lingwei; Min, Jie; Zhang, Jianqi; Wei, Zhixiang; Li, Yongfang
Abstract : High‐efficiency all‐polymer solar cells with less thickness‐dependent behavior are demonstrated by using a low bandgap n‐type conjugated polymer N2200 as acceptor and an absorption‐complementary difluorobenzotriazole‐based medium‐bandgap polymer J51 as donor.